Surge in Measles Cases in Italy from August 2023 to January 2025: Characteristics of Cases and Public Health Relevance - Antonietta Filia; Martina Del Manso; Daniele Petrone; Fabio Magurano; Silvia Gioacchini; Patrizio Pezzotti; Anna Teresa Palamara; Antonino Bella (Vaccines)
Background/Objectives: A resurgence of measles has been observed in Europe and worldwide since 2023. The aim of this article is to describe characteristics of cases reported to the Italian national measles surveillance system and discuss reasons for the outbreak and its public health relevance. Methods: We analyzed measles cases reported to the Italian national measles surveillance system with a symptom onset from August 2023 to January 2025. Results: Overall, 1164 cases were reported, of which 1065 (91.5%) were laboratory confirmed. The median age was 30 years, but the highest incidence was in children under one year of age. Transmission occurred mainly in families and nosocomial settings. Multiple importations occurred during 2023, which initially led to localized outbreaks with limited spread but was subsequently followed by increasing local transmission in 2024. Conclusions: These findings suggest lingering immunity gaps in children and adults in Italy, highlighting the potential severity of measles and the ease with which measles crosses country borders. Besides improving routine immunization coverage, targeted vaccination opportunities should be provided to susceptible population groups. Communication activities are also needed to increase awareness about disease severity, especially among young adults. In view of the upcoming travel season, travel clinics should encourage persons without evidence of measles immunity to be vaccinated before any international travel.